Short-term effects of ambient air pollution and childhood lower respiratory diseases - Liyang Zhu (Nature Portfolio, 2017)
Abstract The association between air pollution and childhood respiratory disease is inconsistent. In the present study, we investigated a short-term effect of ambient air pollutants and daily childhood lower respiratory diseases (CLRD). Daily air pollutants, weather data, and CLRD data were collected from January 2014 to April 2015 (452 days) in Nanjing, China. Time-series regression and generalized additive models were used to assess the effects of air pollutants (PM10, PM2.5, NO2, SO2, O3, and CO) on CLRD. We observed that an interquartile range (IQR) increase in concentrations of PM10, NO2, and SO2 significantly increased the daily CLRD with 6 days cumulative effects (difference of estimates: 2.8%, 95% CI: 0.6–5.0%; 4.1%, 1.2–7.0%; 5.6%, 2.6–8.6%, respectively). However, no significant association was found in IQR concentrations of PM2.5, O3, and CO. Specifically, elevated PM10, PM2.5, NO2, and SO2 significantly increased the numbers of CLRD in cool season (3.6%, 1.5–5.7%; 2.4%, 0.3–4.5%; 4.9%, 2.9–7.0%; 6.3%, 3.7–9.0%, respectively). Additionally, the effect estimates of PM10, NO2, and SO2 in female and age >27 months were more pronounced than in male and age ≤27 months. This study suggested that short-term exposure to ambient PM10, NO2, and SO2 were associated with the increased CLRD numbers.